Gaseous Catalyst Assisted Growth of Graphene on Silicon Carbide for Quantum Hall Resistance Standard Device. Issue 2 (4th December 2022) - Chen, Lingxiu; Wang, HuiShan; Kong, Ziqiang; Zhai, Changwei; Wang, Xiujun; Wang, Yibo; Liu, Zhengtai; Jiang, Chengxin; Chen, Chen; Shen, Dawei; Chen, Xipin; Zhu, Yuxuan; et al.
Abstract: Direct growth of graphene on silicon carbide (SiC) is a very promising method for preparing high‐quality graphene. However, high quality single crystal epitaxial graphene films on SiC always form at a temperature higher than 1800 °C. Here, the synthesis of graphene on the silicon surface (0001) of SiC at ≈1300 °C by gaseous catalyst‐assisted chemical vapor deposition (CVD) method is reported. As the step height of terraces on SiC surface can influence the performance of graphene Hall devices, low‐temperature growth of graphene benefits for keeping the steps of the SiC surface at a small height, which can be achieved by a pre‐treatment before growth. A graphene quantum Hall resistance standard (G‐QHRS) device fabricated on the SiC surface with a small step height of ≈0.5 nm exhibits an accuracy of 1.15 × 10 −8 and a reproducibility of 3.6 × 10 −9 within 7 days in the measurement of quantum resistance at B  = 6 T and T = 4.5 K. The gaseous catalyst‐assisted CVD on SiC is an effective scalable growth approach that produces high‐quality graphene for the resistance metrology, and it represents a promising step toward a low magnetic field QHRS setting the basis of low‐cost and transportable QHRS in a near future. Abstract : High‐quality graphene is fabricated on silicon carbide (SiC (0001)) at ≈1300 °C via gaseous catalyst‐assisted chemical vapor deposition. The growth of graphene at a low temperature can keep the step of SiC terraces at a small height of ≈0.5 nm, and then ensures the successful fabrication of a quantum Hall resistance standard device working under 6 T.